2017
DOI: 10.1016/j.ijscr.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Breast lymphoma in a patient with B-cell Non Hodgkin Lymphoma: A case report study

Abstract: HighlightsBreast involvement in Non Hodgkin Lymphoma is a rare entity.Breast lymphomas represent localized extranodal Primary or Secondary lymphomas.Physical examination is paramount for discovering lesions.Preoperative diagnosis ensures avoidance of unnecessary interventions.Breast lymphomas should be considered in the differential diagnosis of breast neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 14 publications
0
24
1
4
Order By: Relevance
“…Breast lymphoma is a very rare entity, accounting for only 0.1%–0.5% of all breast cancer cases [29, 30]. Further, 0.38%–0.7% of all non-Hodgkin lymphomas (NHL) and 1.7%–2.2% of extranodal NHL cases result in breast metastases [29].…”
Section: Clinical Examplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Breast lymphoma is a very rare entity, accounting for only 0.1%–0.5% of all breast cancer cases [29, 30]. Further, 0.38%–0.7% of all non-Hodgkin lymphomas (NHL) and 1.7%–2.2% of extranodal NHL cases result in breast metastases [29].…”
Section: Clinical Examplesmentioning
confidence: 99%
“…Further, 0.38%–0.7% of all non-Hodgkin lymphomas (NHL) and 1.7%–2.2% of extranodal NHL cases result in breast metastases [29]. The histological type is predominantly B-cell lymphoma, accounting for 85%–95% of all cases, followed by T-cell, Burkitt, mucosa-associated lymphoid tissue lymphoma (MALT), and extranodal natural killer lymphoma nasal types (ENKTL) affecting 5%–15% of patients [30]. In a retrospective study of 204 cases of breast lymphoma, it was found that the age at diagnosis ranges from 50 to 60 years, with a median age at diagnosis of 71 years [31].…”
Section: Clinical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary non-Hodgkin's lymphoma of the breast (PNHL) is a rare entity, accounting for approximately 0.04% to 0.5% of all malignant breast tumors and forming approximately 1.7% to 2.2% of Extra-ganglionic NHL [1] [2] [3]. Their heterogeneity is reflected by various clinical, morphological, immunological and cytogenetic presentations which explain their different classifications.…”
Section: Introductionmentioning
confidence: 99%